Pengaruh Budaya Kerja Terhadap Kinerja Pegawai Di Sekretariat Kabupaten Kutai Timur - Pranawati dan Suyatin (Prodi Ilmu Administrasi Negara, 2016)
This study aims to determine whether a work culture that includes leadership, discipline, motivation, and science and technology affect the performance of employees in the Secretariat of the East Kutai Regency.In this study population is all employees of the Secretariat of the East Kutai Regency, with a total population of 751 people, and the samples taken as many as 75 people. Data in the form of primary data taken using a questionnaire tool. Sampling techniques using Stratified Random Sampling method. The analytical tool used in this research is multiple linear Regression.The results showed that the culture of work which includes leadership, discipline, motivation and science have positive and significant impact on the performance of employees, either partially or jointly. This is indicated by the F test results with a confidence level of 95% has a probability value of 0.000 and the t test all variables have a probability below 0.05. Regression models were formed Y = 0.054 + 0.182 + 0,271.X1 . X2 + 0,303.X3 + 0,270.X4 correlation coefficient ( R) of 0.717 and the determination coefficient 0.514 means that the relationship between work culture and performance of employee has strong relationship. However, there are other variables that have not been able to determine the variation observed that changes in the performance of employees amounted to 48.6 % .